2015
DOI: 10.1021/acs.cgd.5b00218
|View full text |Cite
|
Sign up to set email alerts
|

Two New Adenine-Based Co(II) Coordination Polymers: Synthesis, Crystal Structure, Coordination Modes, and Reversible Hydrochromic Behavior

Abstract: We report the synthesis of two new 3D coordination polymers (CPs) based on Co(II), adenine and aromatic tetracarboxylate linkers. Adenine exhibits bidentate binding modes in both CPs, coordinating through the N3 and N 9 sites in a first compact CP and through the more rare N 3 and N7 sites in a second open, flexible and H2O-responsive CP. These differences together with an analysis of the extended coordination structures made of adenine reported in Cambridge Structural Database illustrate the rich coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…[133] One-dimensional Zn-adeninate chains were formed with adeninate connected to both building units in a 1:1 ratio. [133] In [121,134] The latter structure is shown to have reversible structural transformations upon removal and addition of H2O, giving a color change from pink to purple, respectively. [134] The indication of a color change implies a change in the coordination geometry of Co II from an octahedral to tetrahedral upon removal of coordinated H2O.…”
Section: Nucleobasesmentioning
confidence: 99%
“…[133] One-dimensional Zn-adeninate chains were formed with adeninate connected to both building units in a 1:1 ratio. [133] In [121,134] The latter structure is shown to have reversible structural transformations upon removal and addition of H2O, giving a color change from pink to purple, respectively. [134] The indication of a color change implies a change in the coordination geometry of Co II from an octahedral to tetrahedral upon removal of coordinated H2O.…”
Section: Nucleobasesmentioning
confidence: 99%
“…Nowadays, biomolecules such as nucleobases, amino acids and peptides are preferred over synthetic ligands in the preparation of such compounds . These biomolecules are inexpensive, nontoxic and capable of forming hydrogen bonds, inducing chirality as well as providing multiple donor sites . Interestingly, nucleobases are of prime interests among biomolecules for the construction of CPs.…”
Section: Introductionmentioning
confidence: 99%
“…Among nucleobases, adenine is a more attractive building unit because of its rigid, planar and π‐conjugated structure . Moreover, it offers five potential donor sites including heterocyclic and imidazole nitrogen atoms (Scheme ) which can coordinate many metal ions or form hydrogen bonds and thus leading to new polymeric structures …”
Section: Introductionmentioning
confidence: 99%
“…Adenine, as an important naturally occurring nitrogen heterocycle present in nucleic acids [40], has multiple possible metal-binding modes [41][42][43]. It has been reported that adenine could coordinate with Zn [44], Au [45], Ag [46], Co [47] or Cu [48] to form CPs with diversified morphology and structure. However, most of the researchers just studied the structure of these materials, and very few have studied the encapsulating adaptability of CPs and the activity of guests after they were entrapped.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the researchers just studied the structure of these materials, and very few have studied the encapsulating adaptability of CPs and the activity of guests after they were entrapped. What is more, those CPs that have been reported were formed by harsh reaction conditions, complicated syntheses and with high cost [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%